MnGA with multiple enzyme-like properties for acute wound healing by reducing oxidative stress and modulating signaling pathways - Xueting Guo; Wenqi Wang; Liting Lin; Jie Shan; Junyao Zhu; Shipeng Ning; Hanmei Li; Xianwen Wang; Decheng Lu (Materials Today Bio)
Nanozymes with specific catalytic activity inhibit inflammation and promote wound healing efficiently and safely. In this work, multifunctional manganese-based nanozymes (MnGA) with antioxidant properties were successfully constructed via a simple coordination reaction in which manganese chloride was used as the manganese source and gallic acid (GA) was used as the ligand solution. MnGA possesses both catalase-like (CAT-like) and superoxide dismutase-like (SOD-like) activities and a reactive nitrogen species (RNS) scavenging capacity, which enables it to efficiently inhibit the inflammatory response. Specifically, MnGA scavenges superoxide anions and produces H2O2 via SOD-like activity and then consumes H2O2 to convert it to nontoxic H2O and O2 via CAT-like activity, resulting in a cascade of catalytic reactions to scavenge reactive oxygen species (ROS). Moreover, the scavenging of RNS by MnGA can amplify the anti-inflammatory effect in combination with the scavenging of ROS. RNA sequencing of mouse skin tissue further revealed that MnGA significantly reduces inflammation by modulating the nuclear factor kappa-B (NF-κB), Toll-like receptor (TLR), and NOD-like receptor (NLR) signaling pathways and promotes skin regeneration. In summary, MnGA nanocatalysts possess excellent antioxidative and anti-inflammatory properties, highlighting their potential applications in wound healing and inflammation treatment.